Optoelectronic properties of the two-dimensional van der Waals semiconductor indium selenide (InSe) - Mazumder, Debarati (2022)
This thesis presents an investigation of the optoelectronic properties of the two-dimensional (2D) van der Waals (vdW) semiconductor indium selenide (InSe) and exploits these properties in InSe-graphene vdW heterostructure devices. These heterostructures are fabricated by mechanical exfoliation and dry transfer of InSe and graphene nanosheets. A novel method of device fabrication by needle transfer of graphene microsheets is also described and used for some devices.